Corrosion Behavior of Mild Steel in Seawater from Karangsong & Eretan of West Java Region, Indonesia - Gadang Priyotomo; Lutviasari Nuraini; Siska Prifiharni; S Sundjono (Jurnal Kelautan, 2018)
The corrosion behavior of mild carbon steel, has been investigated using an immersion test and energy-dispersive X-ray spectroscopy in solutions from the sites of Karangsong and Eretan, Northern Coast of West Java Region, Indonesia. As reference, solutions of 3.5% and 5% NaCl were prepared. Salinity, conductivity, and total dissolved solids (TDS) were measured. It was found that uniform corrosion observed on mild steel during the immersion test. Corrosion resistance of alloys decreases with increasing exposure time in natural seawater solutions. Since magnitudes of conductivity, salinity and TDS of all test solutions are similar, it implied that chloride ion have primary role for inducing the corrosion risk of mild steel. That parameter hinders the formation of stable passive film on the surface of corroded mild steel.Key words: conductivity; immersion test; mild steel; salinity; seawater; total dissolved solids.